Strengthening Rural Economies: Governance of Village-Owned Enterprises (BUMDes) for Agricultural Sustainability in Sikka Regency, Indonesia - Andayana, Made Ngurah Demi; Holivil, Ernestus; Rene, Mariayani Oktafiana; Kholikin, Rafi Akhsanul; Konslaus, Karolus (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2024)
This study evaluates the governance practices of Village-Owned Enterprises (BUMDes) in Riit Village, Sikka Regency, focusing on their impact on agricultural productivity and rural development. Adopting a qualitative case study approach, the research highlights how participatory and cooperative governance principles foster community engagement and improve access to agricultural inputs, training, and markets. The findings reveal significant improvements in crop yields and community welfare, especially for cacao and kemiri. However, challenges such as transportation barriers, crop diseases, and limited technological integration hinder the full realization of governance benefits. Bridging these gaps requires capacity-building, infrastructure improvements, and partnerships with external organizations. Drawing from global governance models, this study provides actionable recommendations for enhancing the sustainability and impact of BUMDes operations. These findings contribute to the discourse on rural governance and its role in achieving the Sustainable Development Goals.